2003
DOI: 10.1002/ajmg.a.10027
|View full text |Cite
|
Sign up to set email alerts
|

Unique mosaicism of structural chromosomal rearrangement: Is chromosome 18 preferentially involved?

Abstract: The mentally normal mother of a 4-year-old boy with del(18)(q21.3) syndrome was tested cytogenetically to study the possibility of an inherited structural rearrangement of chromosome 18. She was found to carry an unusual mosaicism involving chromosomes 18 and 21. Two unbalanced cell lines were seen as derivatives of a reciprocal translocation t(18;21), resulting in mosaicism of two cell lines, one with partial monosomy 18q and one with partial trisomy 18q. A literature review revealed that mosaicism of two or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…De Pater et al (2003) suggested that chromosome 18 might carry a high number of certain sequences, which are susceptible to interchromosomal as well as intrachromosomal rearrangements. The most frequent of these abnormalities are deletions and ring chromosome formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De Pater et al (2003) suggested that chromosome 18 might carry a high number of certain sequences, which are susceptible to interchromosomal as well as intrachromosomal rearrangements. The most frequent of these abnormalities are deletions and ring chromosome formation.…”
Section: Discussionmentioning
confidence: 99%
“…Rings often appear as mosaics, as a consequence of the structural instability of the ring during cell division (Baumer et al 2002;Miller et al 2003). There have been reports of cases with chromosome 18 mosaicism, mostly involving chromosome 18 in different cell lines, including r(18), der(18), r(18)x2, monosomy 18 (Stankiewicz et al 2001;De Pater et al 2003;Miller et al 2003;Carreira et al 2007). Overall, these patients with r(18) often share clinical features with del(18q) syndrome, del(18p) syndrome, or their combination, depending on the size of the deletion.…”
Section: Discussionmentioning
confidence: 99%
“…De Pater et al 7 published a case study of a unique mosaicism due to structural chromosomal rearrangement. It was their view that the general 'gene poverty' of chromosome 18 (International Human Genome Sequencing Consortium, 2001) 8 allowed for structural chromosomal rearrangements more frequently compatible with life; this might also be a factor in the unusual gonosomal aneuploidies we report here.…”
Section: A Rare Abnormal Karyotype (45x/47xy+18) Associated With Inmentioning
confidence: 99%
“…In most of them, the abnormal cell line is representative of either an in vitro event or a chromosomal error that is restricted to the extraembryonic tissues, with autosomal trisomy being the most frequent finding (Eisenberg and Wapner, 2002). Structural mosaicism is a rare event, and often difficult to interpret; moreover, chromosome 18 appears to be involved in the majority of such cases (de Pater et al, 2003). In fact, structural abnormalities of chromosome 18 are well documented (Buyse, 1990;Sutcliffe et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, structural abnormalities of chromosome 18 are well documented (Buyse, 1990;Sutcliffe et al, 2001). There are few descriptions of mosaicisms of two unbalanced cell lines, and they mostly concern intra-chromosomal duplication/deletion for the same chromosomal region (de Pater et al, 2003). We report here a prenatal diagnosis of a fetus with mosaicism for two cell lines, each one with a different structural abnormality of chromosome 18; both abnormalities apparently involve the same region of chromosome 18 and may have a common origin.…”
Section: Introductionmentioning
confidence: 99%